HUBUNGAN INSENTIF DAN KESELAMATAN DAN KESEHATAN KERJA (K3)DENGAN KINERJAKARYAWAN PADA PT. PETRO ANTARNUSA KOTA BENGKULU - Nia Indriasari; Tri Hadi Purnomo (UNIVED Press, 2019)
This study aims to determine the relationship of incentives and Occupational Safety and Health (K3) with employee performance at PT. Petro Antar Nusa Bengkulu City. The sample in this research are 32 driver and conductor at PT. Petro Antar Nusa City Bengkulu. Data collection method using questioner and analysis method used is spearman rank correlation and hypothesis test with t test. Incentives have a very strong relationship with employee performance at PT. Petro Antar Nusa Bengkulu City with correlation value of 0.778. This illustrates that the incentives provided by PT. Petro Antar Nusa Bengkulu City can support in improving the performance, because with the incentives will lead to high morale and employees strive to always excel. This is reinforced by hypothesis test result that is tcount bigger than ttable (6,780> 1,697). Thus the result of hypothesis test is H01 rejected and Ha1 accepted. This means that incentives have a significant relationship with employee performance at PT. Petro Antar Nusa Bengkulu City. Occupational safety and health has a strong relationship with employee performance at PT. Petro Antar Nusa City Bengkulu with correlation value of 0.644. This illustrates that with the company's attention to the health and safety of employees of PT. Petro Antar Nusa Bengkulu City will improve the performance of the employees. This is reinforced by the result of hypothesis testing that is tcount is bigger than ttable (4,611> 1,697). Thus the result of hypothesis test is H02 rejected and Ha2 accepted. This means that Safety and Health (K3) has a significant relationship with the performance of employees at PT. Petro Antar Nusa Bengkulu City.